The locoweed endophyte Alternaria oxytropis affects root development in Arabidopsis in vitro through auxin signaling and polar transport. (28th October 2022) - Guan, Huirui; Liu, Xin; Fu, Yanping; Han, Xiaomin; Wang, Yanli; Li, Qing; Guo, Liang; Mur, Luis A J; Wei, Yahui; He, Wei
Abstract: Locoweeds are leguminous forbs known for their toxicity to livestock caused by the endophytic fungi Alternaria sect. Undifilum . Unlike the defensive mutualisms reported in many toxin-producing endophytes and their plant hosts, the benefits that A. sect. Undifilum can confer to it host plants remains unclear. Here, we conducted physiological and genetic analyses to show that A. (sect. Undifilum ) oxytropis influences growth, especially root development, in its locoweed host Oxytropis ochrocephala and Arabidopsis. The presence of A. oxytropis significantly decreased primary root length while increasing the numbers of lateral roots and root hairs, and increasing plant leaf area and fresh weight. The fungus also increased the concentrations of plant endogenous auxin, and the expression of key genes for auxin biosynthesis, signaling, and transport. These effects on root development were abolished in mutants deficient in auxin signaling and polar transport. Alternaria oxytropis down-regulated expression of PIN1 but increased expression of PIN2, PIN7, and AUX1, which might reflect alterations in the spatial accumulation of auxin responsible for the changes in root architecture. Plant growth was insensitive to A. oxytropis when naphthylphthalamic acid was applied. Our findings indicate a function of A. oxytropis in promoting the growth and development of Arabidopsis via the regulation of auxin, which in turn suggests a possible role in benefiting its locoweed hosts via a process independent of its toxin production. Abstract : The endophyte Alternaria oxytropis influences the growth of Arabidopsis seedlings, especially root architecture, via the expression of key plant genes for auxin biosynthesis, signaling, and transport